Kewenangan Pemerintah Aceh terhadap Pelaksanaan Fungsi Mahkamah Syar’iyah dalam Sistem Peradilan Nasional (Tinjauan tentang Kewenangan Yustisi dalam Otonomi Khusus) - Muzakkir Abubakar; Suhaimi Suhaimi; Basri Basri (Kanun Jurnal Ilmu Hukum, 2011)
ABSTRACT: This is the research explaining the legal status of and the existence of the Islamic Law Court in national judicial system, the authority of Aceh Government in enacting the local law derived from Islamic rules as a regulation for the court in acting in national judicial system. The rules would be a guidance for the court in fulfilling the justice for Moslems in Aceh thus the court would be more effective in holding its functions and the constraints faced by the Aceh Government and the court in implementing Islamic Law as a concrete action to fulfil the needed justice in society. The data are gathered by conducting library research and interview with the Islamic Law experts and the experts of criminal justice procedure and civil procedure law which then the data are discussed through.  In order to complete the data gathered from library research, field research is also conducted. The gathered data both from library and field research is analysed by qualitative normative approach then described descriptively.  The findings shows that the Act Number 11, 2006 regarding Aceh Governance has strengthened the legal status and the existence of the court as an Islamic Judicial Court inAceh Province that is apart of the national judicial system. Unlike, the Act Number 18, 2001, the authority that has been conferred to enact substantive and procedural law of the court has not been applied seriously even this is not priority. Therefore, it has not been able to give law certainty and protect the society from undue law process.  The main obstacles faced the practitioners are an unavailable of process law, especially criminal Islamic process law. The Authority of Aceh Government Towards the Conduct of Mahkamah Syar’iyah  in National Judicial System  (A Study on a Judicial Authority in the Context of Special Autonomy)